Wavelet Analysis of Unemployment Rate in Visegrad Countries - Monika Hadas-Dyduch; Michal Bernard Pietrzak; Adam P. Balcerzak (Institute of Economic Research (IER), 2016)
Visegrad countries, Poland, Slovakia, Czech Republic and Hungary have common history and have faced the same challenges created by globalisation process for the last three decades. They have successfully transformed form central planned to market economies. They have implemented fundamental reforms of their whole institutional systems and finally joined the European Union in the year 2004. During this process the most significant changes, which were directly influenced by opening of these economies in the reality of globalisation, have been seen on the labour markets. From the policy point of view the labour markets are always considered as crucial for social and macroeconomic stability of economies. This forces the economists to constant empirical research in this field. In this context the aim of the article is to conduct comparative analysis of the unemployment phenomena in the four countries. For this purpose wavelet analysis was applied. In the research a discrete wavelet transformation was used, which has been recently effectively used for analysis of macroeconomic indicators. The empirical research was conducted for the years 1998-2016 and it was based on the Eurostat data. In the research the following hypothesis was verified: the phenomenon of unemployment in the case of Poland, Slovakia and Hungary is formed in a quite similar way, whereas in Czech Republic the situation on the labour markets is mainly determined by factors of different nature.
Keywords: E2; E24; C45; 330; unemployment; wavelet analysis; multiresolution analysis; Visegrad countries